Immunity profile of hepatitis B antibodies among vaccinated healthcare workers after 10 years of last dose - Zheeno Niyazi Taha; Murad Rasheed Wali; Amal Fadil Mahdi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Hepatitis B virus is a major public health problem causing chronic hepatitis, Health care workers are cosidered at high risk group for being infected from contaminated needles injection, vaccination is the main way to prevent infection with a high protection rate, however testing anti-HBS antibody is important to evaluate the effectiveness of the vaccine as below 10 IU/ml is not protective as the level of the antibody declines. Methodology:This cross-sectional study is based on data collected from health care workers who have been vaccinated within 5, 10 and more than 15 years.Data were collected from January 1, 2024 to March 31,2024 from a total of 90 health care workers who were employed in Azadi teaching hospital. A blood sample was taken from each worker under strict aseptic conditions using a plain vacutainer. Blood was allowed to clot and serum was separated and stored at −20 °C until testing. HBV serum markers (HBsAg, anti-HBs and Interleukin-2) were determined using commercial immuno-enzymatic assays. Results :The level of anti-HBS antibody in the serum of the health care workers were studied to detect weather it is protective or not The ageranging from (25-65) from both genders.The antibody level was obviously decreased after 10 and 15 years of being vaccinated and the result was highly significant. Conclusion:The objective of this study was to evaluate long-term immunogenicity and efficacy of HBV vaccination in two hospitals in health care workers in azadi teaching hospital. An additional objective was to identify the independent predictors of long-termimmunogenicity.